2014
DOI: 10.1155/2014/980429
|View full text |Cite
|
Sign up to set email alerts
|

Association between Follicular Fluid Leptin and Serum Insulin Levels in Nonoverweight Women with Polycystic Ovary Syndrome

Abstract: Aims. We evaluated the links between leptin and visfatin levels and fertilization rates in nonoverweight (NOW) women with PCOS (NOW-PCOS) from Apulia undergoing in vitro fertilization/embryo transfer (IVF). Materials and Methodology. We recruited 16 NOW women with PCOS (NOW-PCOS) and 10 normally ovulating NOW women (control-NOW). All women underwent IVF. Androgens, 17-β-estradiol (17β-E2), and insulin levels were measured in plasma and/or serum and leptin and visfatin levels were assayed in both serum and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…Celik et al showed the presence of leptin resistance at the bloodbrain barrier in preeclamptic pregnant women (65). Gararuti et al reported a significant decline in serum and follicular fluid leptin levels in PCOS (66). Their results were compatible with the study conducted by De Placido et al (67).…”
Section: Resistin and Amylin In Pcossupporting
confidence: 54%
See 1 more Smart Citation
“…Celik et al showed the presence of leptin resistance at the bloodbrain barrier in preeclamptic pregnant women (65). Gararuti et al reported a significant decline in serum and follicular fluid leptin levels in PCOS (66). Their results were compatible with the study conducted by De Placido et al (67).…”
Section: Resistin and Amylin In Pcossupporting
confidence: 54%
“…Exogenous visfatin induces follicle response during ovarian stimulation (142). However, Garruti et al showed normal levels of serum visfatin in PCOS (66). As a conclusion, comprehensive studies are needed to elucidate the effects of these four peptides on subfertility due to PCOS.…”
Section: Cholecystokinin Peptide Yy Incretins Visfatin In Pcosmentioning
confidence: 97%
“…Over the past decade, some studies have investigated the visfatin levels in women with PCOS; in addition, the relationships between visfatin and PCOS characteristics, such as adiposity, IR and androgen levels, have also been the subject of research [8,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Yet, these studies have shown conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…The literature concerning leptin levels are controversial. Certain authors reported lower leptin levels in follicular fluid in anovulatory women with polycystic ovary syndrome (PCOS) (Garruti et al 2014). Others reported increased levels in cases of endometriosis or unexplained reasons for infertility.…”
Section: Resultsmentioning
confidence: 99%